SPATIAL AND TEMPORAL ANALYSIS OF ARIDITY TRENDS USING THE DE MARTONNE INDEX: A GIS-BASED STUDY OF THE TIMGAD BASIN, ALGERIA - Nassim Bella,; Adel Khentouche, (International Journal of Innovative Technologies in Social Science, 2024)
Knowledge of drought conditions is necessary for the rational use of water resources, the prevention of the dangers resulting from them, and for explaining landscape and ecology characteristics. To analyze annual, seasonal and monthly aridity trends in the Timgad Basin, North-East Algeria, climate data from 07 meteorological stations within the 1975-2009 period were used. After computing the De Martonne aridity index at each station, a geographic information system (GIS) was utilized to maps this index throughout the region and specify drought trends, visualizing detected annual, seasonal and monthly tendencies. On an annual scale, the De Marton Drought Index shows a semi-arid climate in the entire Timgad Basin. On a seasonal scale, the winter season shows a dry semi-humid climate - from Mediterranean to semi-humid conditions, and the climate of the region in autumn and spring is semi-arid except for some eastern areas, which are characterized by a dry semi-humid climate - from Mediterranean conditions in spring. In contrast, summer shows from very dry to dry. The period extending from May to October is characterized by a semi-arid to dry climate; December and January reveal humid conditions, while November, February, March and April belong to a semi-arid to Mediterranean climate.